2009
DOI: 10.1371/journal.pgen.1000732
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional Diversity, Non-Random Distribution, and Rapid Evolution of Retroelements in the B73 Maize Genome

Abstract: Recent comprehensive sequence analysis of the maize genome now permits detailed discovery and description of all transposable elements (TEs) in this complex nuclear environment. Reiteratively optimized structural and homology criteria were used in the computer-assisted search for retroelements, TEs that transpose by reverse transcription of an RNA intermediate, with the final results verified by manual inspection. Retroelements were found to occupy the majority (>75%) of the nuclear genome in maize inbred B73.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
380
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 343 publications
(409 citation statements)
references
References 59 publications
(123 reference statements)
26
380
1
2
Order By: Relevance
“…Most of the maize Letter reSeArCH genome is derived from transposable elements 3, 21 , and careful study of a few regions has revealed a characteristic structure of sequentially nested retrotransposons 21,22 and the effect of deletions and recombina tion on retrotransposon evolution 23 . In the annotation of the original maize assembly, however, fewer than 1% of long terminal repeat (LTR) retrotransposon copies were intact 24 . By applying a new homology independent annotation pipeline to our assembly (Extended Data Table 3), we identified 1,268 Mb (130,604 copies) of structurally intact retrotransposons, of which 661 Mb (70,035 copies) are nested retro transposon copies disrupted by the insertion of other transposable elements, 8.7 Mb (14,041 copies) are DNA terminal inverted repeat transposons, and 76 Mb (21,095 copies) are helitrons.…”
Section: Openmentioning
confidence: 99%
“…Most of the maize Letter reSeArCH genome is derived from transposable elements 3, 21 , and careful study of a few regions has revealed a characteristic structure of sequentially nested retrotransposons 21,22 and the effect of deletions and recombina tion on retrotransposon evolution 23 . In the annotation of the original maize assembly, however, fewer than 1% of long terminal repeat (LTR) retrotransposon copies were intact 24 . By applying a new homology independent annotation pipeline to our assembly (Extended Data Table 3), we identified 1,268 Mb (130,604 copies) of structurally intact retrotransposons, of which 661 Mb (70,035 copies) are nested retro transposon copies disrupted by the insertion of other transposable elements, 8.7 Mb (14,041 copies) are DNA terminal inverted repeat transposons, and 76 Mb (21,095 copies) are helitrons.…”
Section: Openmentioning
confidence: 99%
“…For Zea, where repeat sequences have been well-characterized, the repeat groups were then annotated using Cross_Match and five repeat databases (MAGI v3.1, TIGR v2.0 (Ouyang and Buell, 2004), TREP release 7, and the Maize Transposable Element database (Baucom et al, 2009) (http://maizetedb. org/Bmaize/)).…”
Section: Repeat Discovery and Assemblymentioning
confidence: 99%
“…In most angiosperm genomes, the LTR retrotransposons are the most significant contributor to genome size, contributing over 75% of the nuclear DNA to even moderate-sized genomes like maize (Schnable et al, 2009). Most LTR retrotransposons families exist in low copy numbers (SanMiguel and Bennetzen, 1998;Baucom et al, 2009), but the amplification of a few families that individually contribute 4100 Mb of DNA to a genome are the major causes of 'genomic obesity' (Bennetzen and Kellogg, 1997) in plants. LTR retrotransposon amplifications by only one or a few families are sufficient to more than double genome size in a just a few million years, as shown for Oryza australiensis (Piegu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…While TEs only account for ,10% of the Arabidopsis genome [32] or ,32% of the rice genome [33], they contribute ,85% to the maize genome [34]- [35]. Many TEs are located in pericentromeric regions and heterochromatic maize knobs [34], [36], but there are also many TE insertions interspersed between maize genes [37]- [39].…”
Section: Introductionmentioning
confidence: 99%